2023
DOI: 10.1039/d3ta00600j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ru nanoclusters on Co-doped NiSe nanorods with efficient electrocatalytic activity towards alkaline hydrogen evolutionviahydrogen spillover effect

Abstract: The hydrogen spillover strategy was demonstrated to enhance the HER activity of Ru in alkaline electrolytes through Co doping into NiSe. 1.5 wt% Ru–Ni0.85Co0.15Se/NF with a smaller |ΔΦ| value showed a superior HER performance and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…21 Nickel selenides in particular are known to exhibit high catalytic activity and efficiency due to their small bandgap and high degree of covalency between metal-anion bond, 22,23 isfactory when compared with the noble metal-based catalysts. 24 Thus, different approaches were executed to boost the electrocatalytic efficacy of nickel selenides, which include surface treatment, 25 hybridization, 26 heteroatom, or cation doping, 27,28 the addition of conductive supports like graphene oxide, carbon nanotube, etc., 29 and in situ growth of the catalyst on conductive substrates. 30,31 Incorporation of cations into monometallic selenides can tune the electronic properties and modulate the free energy of primitive reactions of hydrogen evolution, which, in turn, would result in augmented electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Nickel selenides in particular are known to exhibit high catalytic activity and efficiency due to their small bandgap and high degree of covalency between metal-anion bond, 22,23 isfactory when compared with the noble metal-based catalysts. 24 Thus, different approaches were executed to boost the electrocatalytic efficacy of nickel selenides, which include surface treatment, 25 hybridization, 26 heteroatom, or cation doping, 27,28 the addition of conductive supports like graphene oxide, carbon nanotube, etc., 29 and in situ growth of the catalyst on conductive substrates. 30,31 Incorporation of cations into monometallic selenides can tune the electronic properties and modulate the free energy of primitive reactions of hydrogen evolution, which, in turn, would result in augmented electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel selenides in particular are known to exhibit high catalytic activity and efficiency due to their small bandgap and high degree of covalency between metal-anion bond, , whereas their electrocatalytic efficacy toward HER is quite unsatisfactory when compared with the noble metal-based catalysts . Thus, different approaches were executed to boost the electrocatalytic efficacy of nickel selenides, which include surface treatment, hybridization, heteroatom, or cation doping, , the addition of conductive supports like graphene oxide, carbon nanotube, etc., and in situ growth of the catalyst on conductive substrates. , …”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic hydrogen production is one of the important ways to produce hydrogen from water molecule due to its green, high efficiency, and stability. [1][2][3][4][5] However, due to the high DOI: 10.1002/smll.202302130 thermodynamic potential and sluggish kinetics of the anodic oxygen evolution reaction (OER), the large-scale production of hydrogen fuel by electrocatalytic water splitting is still a serious obstacle. [6][7][8][9][10] In this context, replacing the OER halfreaction with other more efficient oxidation processes may be a promising approach to improving the overall energy efficiency of water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…In these pioneering reported metal−support HER catalysts, onedimensional nanostructures (e.g., silicon wires) or twodimensional nanosheets (e.g., MoS 2 and graphdiyne), were chosen as the support material. 19,20 For example, by the investigation on a series of Pt alloys and CoP catalysts, it was identified that a small work function difference between metal and support could cause the interfacial charge dilution and relocation, thus weakening interfacial proton adsorption and promoting hydrogen spillover for HER. 21 On the other hand, for metal−support HER electrocatalysts, the hydrogen spillover rate is highly dependent on the metal− support interfaces.…”
mentioning
confidence: 99%
“…Particularly, hydrogen spillover has emerged as an effective contributor to overcome the limitation of the traditional Sabatier’s principle for further improving reaction kinetics during electrocatalytic hydrogen evolution reaction (HER). To achieve the hydrogen spillover effect, binary metal–support electrocatalysts, consisting of an active component with a negative adsorption Gibbs free energy (Δ G H < 0) for strong intermediate adsorption and a support component with a positive energy (Δ G H > 0) for favorable hydrogen release, are required. , A representative example is loading noble-metal particles (e.g., Pt, Ru, Pd, and Ir), on a non-noble-metal-based support (e.g., MoS 2 , CoP, WO 3– x , TiO 2 , and CeO 2 ), which could induce the synergistic effects for hydrogen spillover and meanwhile reduce the utilization of high-cost noble metals without any obvious compromise on the catalytic performance. For the metal component, platinum (Pt) has been intensively chosen as the active site due to the near-zero Δ G H . Nevertheless, rational selection on the suitable support material remains elusive. In these pioneering reported metal–support HER catalysts, one-dimensional nanostructures (e.g., silicon wires) or two-dimensional nanosheets (e.g., MoS 2 and graphdiyne), were chosen as the support material. , For example, by the investigation on a series of Pt alloys and CoP catalysts, it was identified that a small work function difference between metal and support could cause the interfacial charge dilution and relocation, thus weakening interfacial proton adsorption and promoting hydrogen spillover for HER …”
mentioning
confidence: 99%